Toll-like receptor 2 gene polymorphisms, pulmonary tuberculosis, and natural killer cell counts - Tsen Chia-Cheng; Chao Tung-Ying; Eng Hock-Liew; Wu Chao-Chien; Liu Shih-Feng; Chin Chien-Hung; Chen Chung-Jen; Hsiao Chang-Chun; Chen Yung-Che; Wang Yi-Hsi; Lin Meng-Chih (BMC, 2010)
Abstract Background To investigate whether the toll-like receptor 2 polymorphisms could influence susceptibility to pulmonary TB, its phenotypes, and blood lymphocyte subsets. Methods A total of 368 subjects, including 184 patients with pulmonary TB and 184 healthy controls, were examined for TLR2 polymorphisms over locus -100 (microsatellite guanine-thymine repeats), -16934 (T>A), -15607 (A>G), -196 to -174 (insertion>deletion), and 1350 (T>C). Eighty-six TB patients were examined to determine the peripheral blood lymphocyte subpopulations. Results We newly identified an association between the haplotype [A-G-(insertion)-T] and susceptibility to pulmonary TB (p = 0.006, false discovery rate q = 0.072). TB patients with systemic symptoms had a lower -196 to -174 deletion/deletion genotype frequency than those without systemic symptoms (5.7% vs. 17.7%; p = 0.01). TB patients with the deletion/deletion genotype had higher blood NK cell counts than those carrying the insertion allele (526 vs. 243.5 cells/μl, p = 0.009). TB patients with pleuritis had a higher 1350 CC genotype frequency than those without pleuritis (12.5% vs. 2.1%; p = 0.004). TB patients with the 1350 CC genotype had higher blood NK cell counts than those carrying the T allele (641 vs. 250 cells/μl, p = 0.004). TB patients carrying homozygous short alleles for GT repeats had higher blood NK cell counts than those carrying one or no short allele (641 vs. 250 cells/μl, p = 0.004). Conclusions TLR2 genetic polymorphisms influence susceptibility to pulmonary TB. TLR2 variants play a role in the development of TB phenotypes, probably by controlling the expansion of NK cells.